Nanocarriers for Inner Ear Disease Therapy - Xu, Xiaoxiang; Zheng, Jianwei; He, Yanze; Lin, Kun; Li, Shuang; Zhang, Ya; Song, Peng; Zhou, Yuye; Chen, Xiong (Frontiers in Cellular Neuroscience, 2021)
Hearing loss is a common sensory loss disease caused by the diseases in inner ear. The development of delivery systems for inner ear disease therapy is important to achieve high efficiency, and low side effects. Currently, traditional drug delivery systems exhibit potentials to be used for inner ear disease therapy, but there are still some drawbacks. As nanotechnology developing these years, one of the solutions is to develop nanoparticle based delivery systems for inner ear disease therapy. Various nanoparticles, such as soft material and inorganic based nanoparticles, have been designed, tested, and showed controlled delivery of drugs, improved targeting property to specific cells, and reduced systemic side effects. In this review, we summarize recent progress in nanocarriers for inner ear disease therapy. This review will provide useful information on developing promising nanocarriers for efficient treatment of inner ear diseases, and for further clinical applications for inner ear disease therapy.